Skolinių išlikimas tradicinėje šiaurės žemaičių kretingiškių tarmėje - Babickienė, Zofija (Baltistica, 2005)
PRESERVATION OF LOANWORDS IN THE NORTH-ŽEMAITIAN DIALECTAmong the older generation the most productive thematic groups of loanwords are abstract entities, personal names, clothing and footware, buildings and premises. In old writings in most cases alongside the loanword a Lithuanian equivalent may be used. The use of loanwords and their semantic modifications might be due to sociolinguistic and psycholinguistic factors. As a result of psycho-cultural reasons the younger generation tends to use original dialectal loanwords to a much smaller extent.
Keywords: leksika; žemaičiai; kretingiškiai